PLANNING AND INFORMATION SYSTEM DEVELOPMENT STRATEGY USING THE WARD AND PEPPARD METHOD (A CASE STUDY OF CV XYZ) - Ahmad Alfi Adianur Giansyah; Sumardi Sumardi; Mundzir Mundzir; Linda Fauziyah Ariyani (Universitas Mulia, 2022)
To remain competitive globally, businesses must adapt dynamically to changing trends. In response, the necessary action is to implement the use of information technology. While CV XYZ currently has an information system in place, only certain parts of the organization have adopted it, leaving others untouched. Data was gathered through interviews and observations to assess the business environment and the company's information system environment. This research employs the Ward and Peppard method, which includes SWOT analysis, Value Chain analysis, Porter's Five Forces analysis, and McFarlan's Strategic Grid analysis. The study provides strategic recommendations and examines the internal environment, the company's external information systems, and proposed information systems such as HRD information system, After Service information system, Supplier information system, customer service information system, administration information system, and promotion information system. In the McFarlan Strategic Grid mapping, all of these are deemed a priority and feasible for implementation.